ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL PADA MATERI OPERASI BENTUK ALJABAR - Anna Lucia Rengkung; Anekke Pesik; Cori Pitoy (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
English The study aims to analyze the types of errors made by students in solving algebraic operations material questions for class VII SMP Dominico Savio Manado and to find out the factors that cause students to make these mistakes. The type of research used in this research is descriptive qualitative. Data collection techniques were carried out by giving tests and inetrviews. The results of the analysis in this study indicate the types of errors made by class VII students of SMP Dominico Savio Manado in solving problems on the operation material of algebric forms, namely conceptual errors of 66,67%, procedural errors of 55,55%, and computational errors 83,33%. The factors that cause students to make mistakes, namely students do not understand the meaning of the questions given, students are less careful in performing arithmetic operations, and students are in a hurry to solve questions abaout operations in algebraic forms.